Uso da análise da expressão alelo-específica e do efeito de origem parental para a predição de variantes reguladoras de fenótipos relacionados ao músculo de bovinos Bos indicus - Bruscadin, Jennifer Jessica (Universidade Federal de São Carlos, 2025)
The muscle tissue of Nelore cattle (Bos indicus) is the focus of studies aimed at improving meat quality traits that influence consumer acceptance. Therefore, investigating regulatory mechanisms that affect the expression of genes functionally related to these phenotypes is of great importance. Allele-specific expression (ASE) analyses are powerful tools for identifying regions under differential regulatory effects between two alleles, as they highlight the presence of cis-regulatory variants impacting transcription on each haplotype. If the allelic expression depends on the parental origin of the allele, genomic imprinting occurs. Epigenetic and cis-regulatory mechanisms can be responsible for these expression patterns, such as the binding of transcription factors (TFs), microRNAs (miRNAs), and epigenetic mechanisms like DNA methylation when the regulatory SNP is heterozygous. Thus, to analyze the implications of ASE on gene regulation and phenotypic variation in Nelore cattle muscle, this study identified SNPs located in ASE regions (ASE SNPs) across the genome, pointing out those potentially associated with meat quality traits and identifying putative regulatory variants. Furthermore, through analyses of allele-specific methylation (ASM) and association of SNPs with parental origin effects on phenotypes (PO-QTLs, parent-of-origin quantitative trait loci), we suggest potential candidates for genomic imprinting in cattle and their possible impacts on traits of interest. This project identified the largest set of ASE SNPs in bovine muscle to date, comprising 38.177 ASE SNPs, and 24.650 putative cis-regulatory variants (aseQTLs, associated with the ASE and cis-eQTLs, associated to the transcription) able to regulate such expression patterns. The variation in 55 meat quality phenotypes was associated with a total of 1.479 ASE SNPs (referred to as DASE SNPs, differential ASE SNPs) and with 1.817 PO-QTLs. Additionally, 8.074 ASM regions were identified, highlighting new candidate genes for genomic imprinting for future validation. The regulatory mechanisms and biological processes involved in our findings were hypothesized. These results contribute to advancing knowledge about gene regulation in bovine muscle, proposing genomic candidate regions for validation and application in genomic selection programs aimed at improving the meat quality of Nelore cattle.
Use of allele-Specific expression analysis and parent-of-origin effect for predicting regulatory variants of muscle-related phenotypes in Bos indicus cattle
Keywords: Expressão alelo-específica; Melhoramento animal; Genômica; Zebu; Epigenética; Allele-specific expression; Animal breeding; Genomics; Epigenetics; CIENCIAS BIOLOGICAS::GENETICA